(untitled) - Kotler, Philip (Upper Saddle River, N.J., 2003)
This worldwide best-selling book highlights the most recent trends and developments in global marketing-with an emphasis on the importance of teamwork between marketing and all the other functions of the business. It introduces new perspectives in successful strategic market planning, and presents additional company examples of creative, market-focused, and customer-driven action. Coverage includes a focus on customer relationship management, partner relationship management, the Internet and its effects and uses, brand building and brand asset management, alternative go-to-market channels, and marketing around the globe. Chapter topics discuss building customer satisfaction, market-oriented strategic planning, analyzing consumer markets and buyer behavior, dealing with the competition, designing pricing strategies and programs, and managing the sales force For marketing managers who want to increase their understanding of the major issues of strategic, tactical, and administrative marketing-along with the opportunities and needs of the marketplace in the years ahead.
Quản trị Marketing,Marketing nông nghiệp
Keywords: Marketing,Marketing Management,Marketing,Quản trị Marketing